PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT TERHADAP LOYALITAS NASABAH PT. BANK MANDIRI (PERSERO) Tbk, KC DOTULOLONG LASUT MANADO - PUTRI WINDARWATI M. DAHLAN; Johny R. E. Tampi; Tinneke M. Tumbel (Universitas Sam Ratulangi, 2017)
This study aims to determine the influence of Customer RelationshipManagement on customer loyalty in PT. Bank Mandiri (Persero) Tbk, KCDotulolong Lasut Manado. This research is quantitive research using surveymethod. Data collection technique is done by division of questionnaires filled by100 respondents who become the sample in this research. Data collection wasdone with questionnaires that have been tested for validity and reliability. Dataanalysis use is descriptive statistic, consisting of correlation coefficient andsimple regression done by using program SPSS. The result of the research showsthat there is significant influence between Customer Relationship Management oncustomer loyalty. Customer Relationship Management is a very important thingfor the company to establish long-term relationships with customers in order toachieve satisfaction that also impact on customer loyalty, then for the benefit ofthe two parties, the company further improve and optimize the system CustomerRelationship Management to increase customer loyalty.Keyword: Customer Relationship Management, customer loyalty.